2001
DOI: 10.1017/s002531540100426x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and size of Lophelia pertusa coral reefs in mid-Norway in relation to seabed characteristics

Abstract: This paper presents results on the distribution, abundance, and size of Lophelia pertusa coral reefs in mid-Norway (62830 H^6 5830 H N) as compiled from own investigations, earlier scienti¢c reports, reports from ¢shery surveys and ¢shermen. Detailed bathymetrical mapping covering an area of $ 600 km 2 along the Halten gas-pipeline, and two nearby areas across the shelf revealed 70 Lophelia reefs. In general, the reefs occurred close to breaks and escarpments. High densities of up to nine reefs per km 2 were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 18 publications
2
141
0
3
Order By: Relevance
“…This leads to a southward flow that merges with the southward flow of the lower thermocline in the interior of the basin to make up the outflow of Red Sea Water through Bab El Mandeb. Laboratory and field observations have shown that DWC can selectively feed on live zooplankton or suspended particulate organic matter (Mortensen et al, 2001;Freiwald et al, 2002;Kiriakoulakis et al, 2007;Tsounis et al, 2010). Relatively high nutrient levels were observed in the bottom layers (Table 2) compared to the surface layers, which indicates the availability of organic matter.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This leads to a southward flow that merges with the southward flow of the lower thermocline in the interior of the basin to make up the outflow of Red Sea Water through Bab El Mandeb. Laboratory and field observations have shown that DWC can selectively feed on live zooplankton or suspended particulate organic matter (Mortensen et al, 2001;Freiwald et al, 2002;Kiriakoulakis et al, 2007;Tsounis et al, 2010). Relatively high nutrient levels were observed in the bottom layers (Table 2) compared to the surface layers, which indicates the availability of organic matter.…”
Section: Discussionmentioning
confidence: 98%
“…The deep water column at the DWC sites is very homogeneous in terms of temperature (21.6 1C), salinity (40.56) and dissolved oxygen (1.75 ml L À 1 ), with very little seasonal variation (Quadfasel, 2001). Most of the DWC species have been found to inhabit environments with temperatures ranging between 3.5 and 13.5 1C and salinities ranging between 34 and 37 (Mortensen et al, 2001;Freiwald et al, 2002;Taviani et al, 2005). DWC species in the Red Sea live at considerably higher temperatures (420 1C) and salinities (440).…”
Section: Discussionmentioning
confidence: 99%
“…The authors propose a model in which the migration of hydrocarbons into the water column locally "fertilizes" the ambient seawater with organic and inorganic compounds fueling thriving microbial and coral communities. In an alternative hypothesis, several others suggest that external current-and density-controlled mechanisms govern coral reef distribution and growth (Dorschel et al, 2007;De Mol et al, 2002;Frederiksen et al, 1992;Mienis et al, 2007;Mortensen et al, 2001;White et al, 2005White et al, , 2007bWhite, 2007a). This external reef development theory is further supported by the recent study of Dullo et al (2008), which showed a preferential coral settlement, including Røst Reef and Traenadjupet Reef, in water masses of a density of 27.5±0.15 kg/m 3 .…”
Section: Introductionmentioning
confidence: 89%
“…Some, however, are already buried. The main coral species found on the banks, Lophelia pertusa and Madrepora oculata, are known to prefer locations with enhanced current regimes (such as local elevations) and need a hard substrate for their initial settlement (e.g., rock, hardground, a dropstone or piece of coral ;Freiwald 1998;Rogers 1999;Mortensen et al 2001). Furthermore, they tend to live in waters of 4 to 12°C, with a salinity varying between 34 and 37 %c and with a sufficient food supply.…”
Section: Mounds and Coralsmentioning
confidence: 99%